PENERAPAN METODE ROUND ROBIN PADA PEMBELAJARAN PANCASILA MATERI NORMA UNTUK MEMBENTUK SIKAP TANGGUNG JAWAB SISWA KELAS V SEKOLAH DASAR - Nur Azizah, Sitti; Faizal; Alirmansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the application of the Round Robin method in Pancasila learning on norms in shaping the attitude of responsibility of fifth-grade elementary school students. This study is motivated by the low attitude of responsibility of students shown through a lack of active participation, less than optimal learning readiness, and low awareness in carrying out the role as students. This study uses a qualitative approach with a case study type. The research subjects consisted of the fifth-grade homeroom teacher and three fifth-grade students at SD Negeri 95/I Olak. Data were collected through observation, interviews, and documentation. The results of the study indicate that the application of the Round Robin method is able to increase students' active involvement, discipline in discussions, and the development of attitudes of responsibility both academically and socially. This method is effective for use in Pancasila learning on norms to shape students' attitudes of responsibility.